How feeling connected to one's own community can increase support for addressing injustice impacting outgroup communities. (June 2019) - Neufeld, Katelin H. S.; Gaucher, Danielle; Starzyk, Katherine B.; Boese, Gregory D.
How can agents of social change increase public support for minority communities? In three studies, we demonstrate how heightened feelings of community connection can predict support for addressing injustice in minority communities. Community connection, when experimentally evoked (Study 1) or measured (Study 3), was associated with heightened support for the government addressing substandard conditions in an African American housing project (Studies 1 and 3) and Native American reservations (Study 1). Mediation analyses revealed that this effect emerges, at least in part, because of a heightened perceived value of all communities—not merely one's own (Studies 1 and 3). One reason that stronger feelings of community connection lead to (Study 2) or are associated with (Study 3) greater valuing of communities is a strengthened superordinate community identity. We tested additional potential mediators of the community connection–support relationship; out-group identification mediated but outgroup attachment did not. Implications for social change are discussed.